A critique of the use of path dependency in policy studies - Kay, Adrian (2005)
Path dependency is an important notion in diachronic approaches to understanding social and political processes. The first section of this paper examines the application of path dependency to policy studies; the advantages of the concept in understanding policy development are highlighted by examples from pension policy and social housing policy in the UK, and the EU budget. The next section considers several criticisms of path dependency: (1) it is a fashionable label for the institution that `history matters' without a clear and convincing account of decision-making over time; (2) it explains only stability and not change; (3) its normative implications are confused and mostly left unexplored. The final section concludes that path dependency, despite being theoretically inchoate and difficult to operationalize empirically, is a valid and useful concept for policy studies. However, its proper application demands sensitivity from scholars to other temporal dynamics that may operate in policy development. - Reproduced.
Keywords: Public policy